Prawne uwarunkowania mediacji w świetle ustawy o izbach lekarskich - Skelnik, Klaudia; Dana, Andrzej; Jurgilewicz, Marcin (PRAWO i WIĘŹ, 2025)
In the Act of 2 December 2009 on medical chambers, the legislator separated the mediation procedure. This is an institution of mediation, which includes applications within the scope of the physician’s responsibilities. The procedure is initiated as a result of the physician’s failure to perform or improper application. It is a form of control which includes legal consequences related to crime. Disciplinary proceedings are a form of liability for violating a person’s membership of an independent group. In such proceedings, the mediator is only a physician who has been designated as a trustworthy person as part of medical control. However, as mediation proceedings should be conducted by an impartial and neutral person in accordance with the principles appropriate to this institution, normative solutions concerning the application of the Act on legal chambers should be included in this scope.